2007
DOI: 10.1523/jneurosci.2076-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Abstract Ordinal Knowledge in the Horizontal Segment of the Intraparietal Sulcus

Abstract: The anterior intraparietal sulcus, and more specifically its horizontal segment (hIPS), is known to play a crucial role in the cognitive representation of numerical quantity. Whether the involvement of hIPS is restricted to the processing of numerical information or generalizes to non-numerical ordinal dimensions remains an open question. Using functional magnetic resonance imaging during comparison tasks, we demonstrate that the hIPS is equally responsive to numbers and letters, indicating that hIPS is also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
137
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(151 citation statements)
references
References 31 publications
10
137
2
2
Order By: Relevance
“…Another possible interpretation of the effect of temporal distance on IPS activity draws on the idea that the IPS may play a general role in ordinal processing. Distance effects in IPS activity have indeed been observed in many different domains, including numerical and alphabetical processing (Fias, Lammertyn, Caessens, & Orban, 2007;Pinel, Dehaene, Riviere, & LeBihan, 2001), and STM for order (Attout, Fias, Salmon, & Majerus, 2014;Marshuetz, Reuter-Lorenz, Smith, Jonides, & Noll, 2006). These and related findings have led to the view that the IPS (especially the anterior IPS) supports domain general ordinal processes that allow coding for serial order in various task domains (Attout et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…Another possible interpretation of the effect of temporal distance on IPS activity draws on the idea that the IPS may play a general role in ordinal processing. Distance effects in IPS activity have indeed been observed in many different domains, including numerical and alphabetical processing (Fias, Lammertyn, Caessens, & Orban, 2007;Pinel, Dehaene, Riviere, & LeBihan, 2001), and STM for order (Attout, Fias, Salmon, & Majerus, 2014;Marshuetz, Reuter-Lorenz, Smith, Jonides, & Noll, 2006). These and related findings have led to the view that the IPS (especially the anterior IPS) supports domain general ordinal processes that allow coding for serial order in various task domains (Attout et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, Holloway and Ansari (2008) demonstrated that the DE in numerical and non-numerical comparisons is similar, supporting the idea of the DE in comparison reflecting a decisional mechanism. Also neuroimaging studies showed that comparison of number and letter comparison activate very similar parieto-frontal networks in humans, nourishing the idea of common decision mechanisms (Fias, Lammertyn, Caessens, & Orban, 2007). A crucial test would be to investigate the relationship between nonnumerical decision processes and mathematics achievement and dyscalculia.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of humans to process ordinal relationships is not restricted to numerical information, but rather extends to other non-numerical dimensions such as the letters of the alphabet (e.g., Fias, Lammertyn, Caessens, & Orban, 2007;Franklin et al, 2009;Fulbright, Manson, Skudlarski, Lacadie, & Gore, 2003;Gevers, Reynvoet, & Fias, 2003. As such it is a feasible assumption that a relationship between arithmetic and other sequentially organized symbols, such as letters of the alphabet, may exist.…”
Section: Arithmetic?mentioning
confidence: 99%